THE IMPORTANT ROLE OF LAND DEED OFFICIAL IN LAND SALE AND PURCHASE TO AVOID DISPUTES: PERAN PENTING PPAT DALAM JUAL BELI TANAH UNTUK MENGHINDARI ADANYA SENGKETA - Mirda Arifa; Pria Dharsana, I Made (Jurnal Sosial Humaniora, 2022)
A Land Deed Official is a public official who is authorized to make deeds in transfer of land rights, and the authority to encumber mortgage rights in accordance with applicable laws and regulations in Indonesia. However, the question arises as to how significant is the role of Land Deed Official is in the transfer of sale and purchase of land rights, considering the number of land sales and purchases that might have the potential to result disputes in the land sector. This research aims to find out the role of Official Certifier of Title Deeds. in avoiding and resolving disputes in land sale and purchase, and the forms of disputes in land sale and purchase. The method used in this research is normative juridical relating to the legal protection of land sale and purchase agreements. The results of this study are the role of Official Certifier of Title Deeds. in avoiding and resolving disputes in land sale and purchase including; 1) Implementing some land registration activities, 2) Processing the transfer of land rights due to sale and purchase, 3) resolving disputes. In addition, the forms of disputes in land sale and purchase are: 1) Land occupancy without rights. 2) Boundary Dispute, 3) Inheritance Dispute, 4) Repeated Sale and Purchase, 5) Duplicate Certificates. Keywords : land sale and purchase, Land disputes, Certifier of Title Deeds